450 A Shared Cortical Language Network for Multimodal Naming. (April 2023) - Snyder, Kathryn; Forseth, Kiefer; Tandon, Nitin
Abstract : INTRODUCTION: Surgical resections for epilepsy or neoplasms often result in naming deficits. While various brain regions are hypothesized to support separable processes, the language network and its functional mapping to naming remain unclear. However, such knowledge could improve the localization of critical brain regions to preserve language function. METHODS: Data were obtained from epilepsy patients who underwent invasive electrophysiology. Recordings were acquired during three cued-naming tasks using pictures (n = 120), auditory descriptions (n = 82), and orthographic descriptions (n = 68). High-gamma power (65-115Hz) was used to measure activity, and group-level activity was estimated using surface-based mixed-effects multilevel analysis. RESULTS: Analyses showed left-lateralized heteromodal activity in the inferior frontal gyrus (IFG), the middle fusiform gyrus (mFus), and the intraparietal sulcus (IPS) following sensory processing. Activation of mFus peaked 150ms before stimulus offset for auditory (15.2%, p < 10-6) and orthographic (21.4%, p < 10-6) naming and 350ms after picture onset (39.0%, p < 10-6) for visual naming. IPS activation peaked just before stimulus offset for auditory (38.1%, p = 7.7*10-5) and orthographic (27.5%, p = 0.008) naming and 450ms following picture onset (43.0%, p < 10-6) for visual naming. IFG activation peaked just before stimulus offset for auditory (30.1%, p < 10-6) and orthographic (40.1%, p = 10-6) naming and 500ms after picture onset (36.4%, p < 10-6) for visual naming. The left posterior middle temporal gyrus (pMTG) showed heteromodal activity for auditory and orthographic but not visual stimuli with peak activation occurring before convergence of all tasks 250ms before stimulus offset (auditory = 34.1%, p < 10-6;orthographic = 25.5%, p = 0.0035). CONCLUSIONS: These results reveal a heteromodal network of IFG, mFus, and IPS supporting lexical access. Our findings also implicate the role of pMTG in phonological access. Altogether, this work characterizes the roles of key regions within language networks, which could influence surgical approaches to minimize postoperative language deficits.